2008
DOI: 10.1007/s10565-008-9077-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological effect of carbamate molluscicides on the land snail, Eobania vermiculata

Abstract: The present study was designed to investigate the neuropathological effect of the two carbamate pesticides: methomyl and methiocarb on the neurons of the buccal ganglia in the land snail Eobania vermiculata using topical application and baiting technique. Their in vivo effects on acetylcholinesterase (AChE, EC 3.1.1.7) activity were also investigated. Sublethal dose and concentration (1/4 LD(50) and 1/4 LC(50)) of both pesticides were used, and the experiment lasted for 14 days. Histopathological and ultrastuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The results of present study showed important inhibition of AChE activity in snails E. vermiculata exposed to organic pollutants, with the most important reduction detected in the higher exposure concentrations (1 ppm) of the organophosphate insecticides chlorpyrifos and parathion-methyl in the digestive cells. The previous observation is probably related to the particularly fast interaction of these organic substances with AChE, as competitive inhibitors of this enzyme, as it has been also proposed by Essawy et al (2008), after the study of snails E. vermiculata, which is in agreement with Pessah and Sokolove (1983) and Young and Wilkins (1989). The neurotoxic action of organics is owed to the inhibition of AChE activity and the accumulation of acetylcholine in the synaptic connections that can lead to changes of movement ability (Wedgwood and Bailey 1988) and diet (Bailey 1989).…”
Section: Effects Of Organic Pollutants On Eobania Vermiculata 1489supporting
confidence: 82%
“…The results of present study showed important inhibition of AChE activity in snails E. vermiculata exposed to organic pollutants, with the most important reduction detected in the higher exposure concentrations (1 ppm) of the organophosphate insecticides chlorpyrifos and parathion-methyl in the digestive cells. The previous observation is probably related to the particularly fast interaction of these organic substances with AChE, as competitive inhibitors of this enzyme, as it has been also proposed by Essawy et al (2008), after the study of snails E. vermiculata, which is in agreement with Pessah and Sokolove (1983) and Young and Wilkins (1989). The neurotoxic action of organics is owed to the inhibition of AChE activity and the accumulation of acetylcholine in the synaptic connections that can lead to changes of movement ability (Wedgwood and Bailey 1988) and diet (Bailey 1989).…”
Section: Effects Of Organic Pollutants On Eobania Vermiculata 1489supporting
confidence: 82%
“…Such vacuoles were regarded as a cellular defense mechanism against injurious substances that segregated in the vacuoles. [11] The second interesting finding in our study is that the cerebral endothelial cells became swollen and blocked the lumen of the capillary [Figure 4]. Higher magnification of cerebral endothelial cells is shown in Figure 5.…”
Section: Resultsmentioning
confidence: 62%
“…Enhanced autophagy in mussel digestive cells has been considered as a cellular defense against environmentally induced oxidative stress (Moore 2008). Besides, increased number of autophagosomes was found in the CNS of another mollusk species, the land snail Eobania vermiculata, following pesticide treatment in vivo (Essawy et al 2009). …”
Section: Discussionmentioning
confidence: 99%